Transcription of the chicken myb proto-oncogene starts within a CpG island - Dvorák, M; Urbánek, P; Bartůnĕk, P; Paces, V; Vlach, J; Pecenka, V; Arnold, L; Trávnicek, M; Ríman, J (Nucleic acids research, 1989)
The nucleotide sequence of an 8.2-kb DNA fragment from the 5' proximal part of the chicken myb proto-oncogene spanning 1761 nucleotides upstream and 6436 nucleotides downstream from a presumed c-myb initiation codon was determined. A 3.3-kb G + C-rich region found in this sequence had also other features characterizing CpG islands, i.e. no CpG underrepresentation and lack of CpG methylation. In haematopoietic tissues c-myb mRNA synthesis starts in two major regions of the CpG island, namely 98 to 108 and 143 to 145 nucleotides upstream from the c-myb initiation codon. These two regions are in or close to the 124-bp evolutionarily conserved element located in the middle part of the CpG island. No alternative splicing of the 5' end of c-myb mRNA suggested earlier (1,2) was observed. The c-myb promoter contains neither TATA nor CAAT box-like structures at the usual positions. Instead, numerous potential Sp1 factor binding sites were found both upstream and downstream from the transcription initiation sites. Moreover, consensus v-myb protein DNA-binding sites were revealed in the promoter region and in sequences downstream from it.
Keywords: kur domácí; RNA Caps; sekvence nukleotidů; Proto-Oncogene Proteins c-myb; Male; Sequence Homology, Nucleic Acid; Endonucleases; Chickens; Cloning, Molecular; restrikční mapování; Transcription, Genetic; Organ Specificity; Restriction Mapping; Thymus Gland; klonování DNA; Dinucleoside Phosphates; Proto-Oncogene Proteins; molekulární sekvence - údaje; Proto-Oncogenes; dinukleosidfosfáty; sekvenční homologie nukleových kyselin; promotorové oblasti (genetika); mužské pohlaví; thymus; Single-Strand Specific DNA and RNA Endonucleases; RNA čepičky; protoonkogeny; genetická transkripce; endonukleasy; Animals; protoonkogenní proteiny c-myb; zvířata; endonukleasy specifické pro jednořetězcové nukleové kyseliny; Promoter Regions, Genetic; erytrocyty; myši; Erythrocytes; Molecular Sequence Data; Base Sequence; Mice; orgánová specificita; protoonkogenní proteiny